Penggunaan metode drill dalam meningkatkan pembelajaran tata boga pada siswa dengan hambatan pendengaran - Reza Febri Abadi; Toni Yudha Pratama; Cindy Aditya Lestari (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2020)
This study aims to determine the use of the drill method application in improving culinary learning in students with hearing loss study with the design of a pre-test group post-test Class VII in SKh Negeri 02 Serang City Banten), This study is an experimental study using one group approach pretest-posttest. The subjects in this study were deaf students in class VII with a total of 3 students at State College 02, Serang city. The instrument used in using the drill method is a performance test in the form of a psychomotor assessment sheet in accordance with the target behaviour to be achieved. The results showed the average value of students 'initial psychomotor abilities (pretest) 32, after studying the average value of students' final psychomotor abilities (posttest) to 87. The results of statistical tests showed that the use of the drill method could improve culinary learning in making rainbow cakes in students with hearing loss in class VII in SKh 02 Serang City, Banten. Based on the results of research on the use of the drill method in the procurement of good skills making the rainbow cake to students with hearing impairment in class VII at Skh 02 city of Serang Banten, the drill method is hampered against the ability to make the acquisition of rainbow cake baking skills, this is indicated by the increasing increase.